Advances in Hematologic Malignancies - Abdul Hamid, Gamal (IntechOpen, 2019)
The book Advances in Hematologic Malignancies presents new knowledge of cellular disease processes, molecular pathology, and cytogenetic, epigenetic, and genomic changes that have influenced the current outlook toward hematological malignancies. This book provides a unique, practical, and concise guide that is focused on the must-know points of diagnosis, prognosis, therapeutic management, and cutting edge clinical trial opportunities for each hematologic malignancy. Advances in Hematologic Malignancies is designed and organized as an essential reference source for the hematologist, hematologic oncologist, hematopathologist, and trainee.